Viabilidade e longevidade de sementes de Tabebuia aurea Benth. & Hook. submetidas a diferentes métodos de armazenamento - Neves, Graciele [UNESP]; Serigatto, Edenir Maria; Dalchiavon, Flávio Carlos; Silva, Celice Alexandre (My University, 2014)
Seeds Tabebuia aurea (syn. Handroanthus aureus Mattos), The seeds of Tabebuia aurea (syn. Handroanthus Mattos aureus), have low metabolic rates, which favors their storage conditions and freezing temperatures when stored at room temperature, there is a progressive decline in viability. Therefore, this study aims to determine the viability and longevity of seeds of Tabebuia aurea subjected to different storage methods. There were used 6100 seeds. In 2400 seeds were stored refrigerator, which in 1200 placed in transparent plastic bag and 1200 in Kraft paper bags. 3600 Other seeds were placed in room temperature and 1200 seeds in clear plastic bag, 1200 in Kraft paper bags and tray open in 1200. For each treatment, four replicates of 25 seeds for 12 months, with design was completely randomized. The average germination, normal seedlings and speed germination index were transformed into (x+1)-1/2. The data were submitted to ANOVA and means compared by Tukey test at 5%. Also regressions polynomials were modeled for the variables study in function of the periods of storage of the seeds. The seeds stored in the refrigerator at 13 °C maintained a high germination rate and normal seedling germination rate during the 360 days of evaluation. The method suitable for the seed storage of Tabebuia aurea is in the refrigerator at 13 °C, both in plastic and paper.
Viability and longevity of seeds Tabebuia aurea Benth. & Hook. under different storage methods
Keywords: Bignoniaceae. germination. temperature